Extracorporeal Detoxification in Victims with Severe Concomitant Injury - S. Ye. Khoroshilov; N. A. Karpun; A. M. Ilychenko; A. V. Nikulin; S. G. Smirnova; R. Ye. Pavlov (Общая реаниматология, 2009)
Objective: to improve the results of victims with massive crushes of soft tissues in severe concomitant injury (SCI), by applying extracorporeal detoxification techniques as soon as possible. Subjects and methods. The results of examination and treatment were studied in 41 victims with SCI treated at the N. N. Burdenko Main Military Clinical Hospital in 2006 to 2008. In the early posttraumatic period (on days 1—3), all the victims (n=41) were divided into 2 groups. Group 1 victims (n=19) underwent hemodiafiltration (HDF) with replacement at 35 ml/kg/hr; Group 2 (n=22) had plasmapheresis. Results. Early HDF applied to Group 1 victims could achieve 32, 44, and 37% reductions in the elevated levels creatine phosphokinase, myoglobin, and middle-sized molecules, respectively. In Group 2, plasmapheresis showed a lower effect (19, 25, and 26% reductions). Furthermore, there was a decrease in total protein in Group 1, which was absent in Group 2. Conclusion. The timely use of extracorporeal detoxification techniques in victims with massive crushes of soft tissues in the early posttraumatic period prevents the development of fatal complications of SCI, at the same time HDF is more effective and safe than plasmapheresis. Key words: severe concomitant injury, rhabdomyolysis, myoglobin, plasmapheresis, hemodiafiltration.